24.8k views
4 votes
Find the derivative of f(x)= e^(4x) + e^-(4x)

User Garric
by
7.0k points

2 Answers

3 votes

Answer:

Explanation:

note : (e^(u(x))' = (u(x))'e^(u(x)

f(x)= e^(4x) + e^-(4x)

f'(x) =4e^(4x) - 4 e^-(4x)

User Nauman Tariq
by
6.6k points
3 votes

Answer:


f'(x)=4e^(4x) -4e^(-4x)

Explanation:

To find this derivative, we will need to use the chain rule.

As there is a variable in the exponent we can use this formula:


f'(x)=u'e^u

In this case,
u=4x and
u=-4x

This means that
u'=4 and
u'=-4 respectively

This gives us
f'(x)=4e^(4x) -4e^(-4x)

User Joacoleza
by
7.0k points